PEDAGOGICS OF PARTNERSHIP AS THE FUNDAMENTAL FOUNDATIONS OF THE ORGANIZATION OF INCLUSIVE EDUCATION OF YOUNGER SCHOOL STUDENTS - Matveieva, Nataliia; Klepar, Maria; Nych, Oksana (Mountain School of Ukrainian Carpaty, 2023)
The article emphasizes the importance of pedagogy of partnership and cooperation in the organization of education, upbringing and development of younger schoolchildren with special educational needs. The purpose of the article is to demonstrate the importance of partnership pedagogy in creating favorable conditions for learning, upbringing and development of younger schoolchildren with special educational needs in the conditions of a general secondary education institution. The methodological basis of the study is a systematic approach to the analysis of the organization of inclusive education of primary school students with special educational needs, integrated into general secondary education institutions on the basis of partnership pedagogy. The following general scientific methods were used during the research: comparative analysis of scientific, educational and methodological sources, normative and legal basis of inclusive education in Ukraine; theoretical and empirical methods (questionnaire and conversations with students, teachers, parents; observation, pedagogical experiment, data processing, and others), methods of generalization. Emphasis is placed on the types of social partnership, their directions of implementation in the practical activities of specialists of an educational institution with inclusive education. The main criteria and indicators of partnership interaction are highlighted, the requirements for the activities of teachers and other specialists to increase the effectiveness of cooperation in the conditions of an inclusive environment are emphasized. The scientific novelty of the obtained results lies in the systematization of views on the problem of establishing partnership interaction in the process of education, upbringing and development of younger schoolchildren with special educational needs; identification of current problems and prospects for improving the effectiveness of inclusive activities of schools based on partnership and cooperation of participants in the educational process. It has been established that the indicators of effective learning, upbringing and development of younger schoolchildren with special needs are the creation of a favorable atmosphere in an educational institution, the establishment of friendly interpersonal relationships, and the organization of the educational process on the basis of partnership. The advantages of socio-pedagogical partnership and cooperation in comparison with traditional forms of interaction of the administration, teachers of the educational institution with parents of students, the public and extracurricular institutions are revealed.